The EU and the Balkans: From association to membership? - Marie-Janine Calic (Stiftung Wissenschaft und Politik (SWP), 2003)
Despite more recent overseas challenges, the Balkans still figure prominently on the EU's foreign policy agenda. But new political priorities, financial constraints, and the implications of enlargement require a thorough reassessment of the Union's approach to the region. The upcoming EU-Western Balkans summit in Salonica in June 2003 offers an opportunity for evaluating strategies and goals, and adjusting instruments to new circumstances. This paper recommends reinforcing complementarity between the EU's main integrative processes for the Western Balkans, in particular the Stabilisation and Association Process (SAP) and the Stability Pact; to give the EU-accession dimension greater weight within the SAP; and to reduce the region's dependency on aid by substituting external assistance with indigenous growth.(SWP Comments / SWP)
Keywords: 320